2021
DOI: 10.1371/journal.pone.0249970
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of a screening tool for autism in the community—The Indian Autism Screening Questionnaire (IASQ)

Abstract: Introduction Currently available screening questionnaires for Autism spectrum disorders were tested in developed countries, but many require additional training and many are unsuitable for older individuals, thus reducing their utility in lower/ middle- income countries. We aimed to derive a simplified questionnaire that could be used to screen persons in India. Methods We have previously validated Indian Scale for Assessment of Autism (ISAA), that is now mandated for disability assessment by the Government … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Our earlier manuscript reported that at a cut-off of 1, sensitivity was 99%, specificity 62%, Positive Predictive Value 81%, and Negative Predictive Value 95%. In the present, more diverse sample, sensitivity and specificity are 97.5% and 83.7% respectively [ 11 ]. Although the current samples were different from our earlier clinic sample, results remained fairly consistent and acceptable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our earlier manuscript reported that at a cut-off of 1, sensitivity was 99%, specificity 62%, Positive Predictive Value 81%, and Negative Predictive Value 95%. In the present, more diverse sample, sensitivity and specificity are 97.5% and 83.7% respectively [ 11 ]. Although the current samples were different from our earlier clinic sample, results remained fairly consistent and acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…Sociodemographic data sheet, developmental milestones information sheet (both from the ISAA manual), Indian Autism Screening Questionnaire (IASQ) [ 11 ], the Indian Scale for the Assessment of Autism (ISAA) [ 19 ] and Childhood Autism Rating Scale 2 (CARS2) [ 14 ] were administered to all the participants.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The autism spectrum screening questionnaire (ASSQ) is one of the screening tools for ASD (Bernie et al, 2021;Chakraborty et al, 2021;DuBay et al, 2021;Lord et al, 2022;Scott et al, 2021;Yan et al, 2021). It was originally designed by Ehlers and Gillberg, with further refinement in collaboration with Lorna Wing for the purpose of estimating prevalence of Asperger's syndrome (Ehlers et al, 1999).…”
mentioning
confidence: 99%